Analisis Kesalahan Ejaan pada Penelitian Karya Ilmiah Mahasiswa - Oktaviani, Riska; Ramdhani, Intan Sari (ALSYS, 2022)
The purpose of the study was to describe the use of punctuation in scientific works of students of the Language Education Study Program and Indonesian Literature, Muhammadiyah University, Tangerang. The research carried out is qualitative descriptive research. The object of research is a student's scientific work Indonesian Language and Literature Study Program semester VI with data and sources data in the form of research paper assignments. Data collection using studies documentary. The data analysis technique used is descriptive qualitative. Results research shows errors contained in student paper research in the form of using the wrong punctuation to cause ambiguous sentences.